2018
DOI: 10.1002/admi.201801099
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed Laser Induced Triple Layer Copper Oxide Structure for Durable Polyfunctionality of Superhydrophobic Coatings

Abstract: anions such as chloride ions. [1,2,[4][5][6][7] This can compromise using bare copper and its alloys in technology because corrosion of copper impacts its performance in industrial and technological applications.Several ways for enhancing the corrosion protection were discussed in the literature, including the formation of thick oxide films [3,8,9] and the formation of a superhydrophobic layer atop of bulk copper. [10][11][12][13][14][15][16][17][18][19] As for oxide films on copper and copper alloys, typicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…Meanwhile, the current density began to decrease, possibly due to the electrochemical oxidation or electro corrosion that occurred on component 1c through accumulated electroinduced holes, and then it kept up a durative datum. 58 Apparently it exhibited outstanding long-term operation stability beyond 40 h (Fig. 5b).…”
Section: R E T R a C T E Dmentioning
confidence: 92%
“…Meanwhile, the current density began to decrease, possibly due to the electrochemical oxidation or electro corrosion that occurred on component 1c through accumulated electroinduced holes, and then it kept up a durative datum. 58 Apparently it exhibited outstanding long-term operation stability beyond 40 h (Fig. 5b).…”
Section: R E T R a C T E Dmentioning
confidence: 92%
“…Here, soaking of the deposited liquid into the porous surface structure forces the bacteria against the hierarchically scaled surface features resulting in structural cell membrane damage, [38][39][40] similar to the killing mechanism of bacteria piercing surface topographies on Cicada or Dragonfly wings. [32,33] Unfortunately, antibacterial efficiency decreases strongly as soon as the surfaces stabilize at hydrophobic wetting, [38,41] which is most likely linked to the dense superficial layer of CuO initiated during short pulsed laser processing [42] showing reduced antimicrobial capacities due to reduced Cu ion release. [14] Therefore, it is important to include all functional aspects of their antiseptic effectiveness when specifically optimizing antimicrobial copper surfaces in order to maintain the positive effects over a longer period of time.…”
Section: Introductionmentioning
confidence: 99%
“…Laser technology allows easily achieving the extreme water repellence for the diversity of materials. Besides, it was also shown that a combination of laser chemical modification and laser texturing followed by chemisorption of low surface energy compounds allows getting the superhydrophobic coatings with exceptional mechanical and chemical properties on top of different substrates [17][18][19][20]. Thus, providing breakthrough results in Metals 2021, 11, 41 2 of 14 materials science [21][22][23][24][25][26][27][28], laser processing of materials has proven to be a quite simple and attractive method for surface modification.…”
Section: Introductionmentioning
confidence: 99%